2012
DOI: 10.4049/jimmunol.1103425
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus Infection-Associated Downregulation of C-Type Lectin-Related-b Prevents NK Cell Inhibition by NK Receptor Protein-1B

Abstract: Innate immune recognition of virus-infected cells includes NK cell detection of changes to endogenous cell-surface proteins through inhibitory receptors. One such receptor system is the NK cell receptor protein-1B (NKR-P1B) and its ligand C-type lectin-related-b (Clr-b). NKR-P1B and Clr-b are encoded within the NK cell gene complex, a locus that has been linked to strain-dependent differences in susceptibility to infection by poxviruses. In this study, we report the impact of vaccinia virus (VV) and ectromelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…In agreement with this, similar findings were reported for mClr-b in a mouse model of orthopoxvirus (VV, ECTV) infection [15] . Here, we provide evidence for a conserved mechanistic response for both mClr-b and rClr-11 in response to cross-species CMV infection.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In agreement with this, similar findings were reported for mClr-b in a mouse model of orthopoxvirus (VV, ECTV) infection [15] . Here, we provide evidence for a conserved mechanistic response for both mClr-b and rClr-11 in response to cross-species CMV infection.…”
Section: Discussionsupporting
confidence: 80%
“…We next tested the effects of the proteasomal inhibitor, MG132, on MCMV infection-mediated Clr-b loss, as we previously showed that inhibition of the Ub-proteasome degradation pathway could prevent genotoxic stressmediated Clr-b downregulation [14,15] . MG132 was effective at blocking MCMV-mediated Clr-b loss, albeit incompletely even at high doses (online suppl.…”
Section: Mcmv-mediated Mclr-b Downregulation Is Partially Blocked By mentioning
confidence: 99%
See 1 more Smart Citation
“…The murine NKR-P1B ligand, , is rapidly lost in response to cellular infection by diverse viruses Voigt et al, 2007;Williams et al, 2012). However, MCMV-infected fibroblasts also induce a Clr-b-independent NKR-P1B ligand .…”
Section: Encodes An Nkr-p1b Decoy Immunoevasinmentioning
confidence: 99%
“…Yet to date, NKR-P1C, the prototypical NK1.1 antigen in B6 mice (Glimcher et al, 1977;Koo and Peppard, 1984;Ryan et al, 1992), and NKR-P1A remain orphan-activating receptors with unknown physiological ligands. On the other hand, the paired NKR-P1F and NKR-P1G receptors recognize overlapping ''self'' Clr (Clec2) ligands to balance signals during NK cell education and effector responses, while the inhibitory NKR-P1B receptor recognizes the broadly expressed self Clr-b (Clec2d) ligand (Carlyle et al, 2004;Chen et al, 2011;Iizuka et al, 2003;Kveberg et al, 2009 been shown to be involved in ''missing-self'' recognition under diverse pathological states (Kirkham and Carlyle, 2014), including cancer (Carlyle et al, 2004), genotoxic and cellular stress (Fine et al, 2010), hematopoietic transplantation , immune escape of primary lymphoma cells , and cytomegalovirus and poxvirus infection Voigt et al, 2007;Williams et al, 2012), while the remainder of the self Clr ligands remain less well characterized. Among pathogens recognized by NK cells, cytomegaloviruses (CMV) demonstrate co-evolution with their natural hosts, likely due to cycles of natural selection for viral versus host fitness.…”
Section: Natural Killer (Nk) Cells Are a Subset Of Innate Lymphoid Cementioning
confidence: 99%